Association of Spiritual Well-Being and Parental Acceptance with Child Behavioral Disorders through the Mediation of Life Satisfaction in Mothers of Children with Hearing Impairment - Maryam Pourseyyed Mohammad; Farah Naderi; Parvin Ehteshamzadeh; Parviz Asgari (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Mothers' awareness of their negative feelings and emotions, such as anxiety and stress, has a powerful impact on improving life satisfaction and reducing children's behavioral disorders. Objectives: The present study was done to investigate the association between spiritual well-being and parental acceptance and child behavioral disorders through the mediation of life satisfaction in mothers of children with hearing impairment. Methods: This research was a descriptive correlational study performed by path analysis. The statistical population included all mothers of children with hearing impairment in Tehran city, of whom 284 cases were selected as the sample using convenience sampling. The research instruments included the Porter Parental Acceptance Scale (PPAS), the Spiritual Well-Being Scale (SWBS), Behavior Disorders Questionnaire (BDQ), and the Satisfaction with Life Scale (SWLS). The proposed model was evaluated using path analysis by SPSS Amos 24.0. Results: The results showed that there was a significant association between spiritual well-being and child behavioral disorders (p<0.01), spiritual well-being and life satisfaction (p<0.01), parental acceptance and life satisfaction (p<0.01), and life satisfaction and child behavioral disorders (p<0.01). There was no significant association between parental acceptance and child behavioral disorders (p>0.05). The results of path analysis indicated that life satisfaction played a mediating role in the association between spiritual well-being and parental acceptance with child behavioral disorders (p<0.01). Conclusion: According to the results, the proposed model had a good fit. Accordingly, by strengthening and improving spiritual well-being, parental acceptance and life satisfaction can improve the behavioral disorders of children with hearing impairment.